Process-Based Management in Public Administration: A Bibliometric Analysis - Gilbert Roland Alvarado-Arbildo; Hugo Henry Ruiz-Vásquez; Stevs Raygada-Paredes; Víctor Arturo Jesús Castillo-Canani; Beny Pasquel-Flores; David Eduardo Burga-Pérez; Wu Koy Fon Chonn-Chang; David Miguel Melgarejo-Mariño; Edgar David Iturrarán-Sandoval; José Ricardo Young-Gonzales (Emerging Science Journal, 2025)
This bibliometric study aimed to analyze the trends and scope of scientific papers on process-based management in public administration worldwide between 2010 and 2024. A methodology based on the Scopus search engine was used to collect the data, which were selected according to specific criteria; thus, 29 documents were obtained. For the analysis, Microsoft Excel was used to produce graphs and tables, and VOSviewer software was used to create co-occurrence maps of countries, authors, and keywords. The results indicated that the United States and Brazil were the most productive countries in this area. Most papers were published as conference papers in areas such as computer science, business management, engineering, and social sciences, while scientific papers were the most cited. It was identified that process-based management has been applied in various sectors, such as healthcare institutions, educational institutions, food companies, and agricultural companies, among others. It was concluded that the reviewed papers highlight the obstacles derived from the organizational and operational complexity in public sector institutions, which limits the implementation of process-based management. This underlines the need for further research, especially for comparisons with private sector organizations.